Pluripotent Stem Cells From the Bench to the Clinic - Tomizawa, Minoru (IntechOpen, 2016)
Pluripotent stem cells have distinct characteristics: self-renewal and the potential to differentiate into various somatic cells. In recent years, substantial advances have been made from basic science to clinical applications. The vast amount knowledge available makes obtaining concise yet sufficient information difficult, hence the purpose of this book. In this book, embryonic stem cells, induced pluripotent stem cells, and mesenchymal stem cells are discussed. The book is divided into five sections: pluripotency, culture methods, toxicology, disease models, and regenerative medicine. The topics covered range from new concepts to current technologies. Readers are expected to gain useful information from expert contributors.